Metabolic disorders and the risk of cholangiocarcinoma. (2nd September 2021) - Ghidini, Michele; Ramai, Daryl; Facciorusso, Antonio; Singh, Jameel; Tai, Waqqas; Rijavec, Erika; Galassi, Barbara; Grossi, Francesco; Indini, Alice
ABSTRACT: Introduction : Cholangiocarcinoma (CCA) is a malignancy which arises from the biliary epithelium. Carcinogenesis of CCA is mainly linked to aberrant glucose metabolism and creation of an immunosuppressive environment around normal biliary epithelium. The incidence of CCA is higher in the East due to Opisthorchis viverrini, an endemic liver fluke. CCA has also be attributed to genetic, metabolic, and lifestyle risk factors. Areas covered : Differences in epidemiological risk factors are associated with varying phenotypes of CCA. Metabolic risk factors include diabetes, obesity, nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH), dyslipidemia, and metabolic syndrome. Inherited metabolic risk factors include Wilson's disease and hemochromatosis. Metabolic disease is associated with a higher risk of CCA, with higher risk for the intrahepatic form. In this review, the authors provide an overview of available evidence regarding metabolic conditions associated with the development of CCA. Expert opinion : Metabolic disease is associated with a higher risk of intrahepatic CCA compared to its extrahepatic or hilar counterpart. As rates of obesity and metabolic syndrome increase, particularly in the West, it is conceivable that the incidence of CCA will also rise in the next years.